Formulation and Characterization of Hesperidin-Loaded Transethosomal Gel for Dermal Delivery to Enhance Antibacterial Activity: Comprehension of In Vitro, Ex Vivo, and Dermatokinetic Analysis - Perwez Alam; Mohd Imran; Samreen Jahan; Ali Akhtar; Zafrul Hasan (Gels, 2023)
In this study, hesperidin was loaded into a transethosome and was developed employing the rotary evaporator method. The formulation was optimized using the Box–Behnken design (BBD). The optimized HSD-TE formulation has a spherical shape, vesicle size, polydispersity index, entrapment efficiency, and zeta potential within the range of 178.98 nm; the PDI was 0.259 with a zeta potential of −31.14 mV and % EE of 89.51%, respectively. The in vitro drug release shows that HSD-TE exhibited the release of 81.124 ± 3.45% in comparison to HSD suspension. The ex vivo skin permeation showed a 2-fold increase in HSD-TE gel permeation. The antioxidant activity of HSD-TE was found to be 79.20 ± 1.77% higher than that of the HSD solution. The formulation showed 2-fold deeper HSD-TE penetration across excised rat skin membranes in confocal laser microscopy scanning, indicating promising in vivo prospects. In a dermatokinetic study, HSD-TE gel was compared to HSD conventional gel where TE significantly boosted HSD transport in the epidermis and dermal layers. The formulation showed greater efficacy than free HSD in the inhibition of microbial growth, as evidenced by antibacterial activity on the Gram-negative and positive bacteria. These investigations found that the HSD-TE formulation could enhance the topical application in the management of cutaneous bacterial infections.